The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1995
DOI: 10.1152/jn.1995.74.4.1787
|View full text |Cite
|
Sign up to set email alerts
|

Motor adaptation to Coriolis force perturbations of reaching movements: endpoint but not trajectory adaptation transfers to the nonexposed arm

Abstract: 1. Reaching movements made in a rotating room generate Coriolis forces that are directly proportional to the cross product of the room's angular velocity and the arm's linear velocity. Such Coriolis forces are inertial forces not involving mechanical contact with the arm. 2. We measured the trajectories of arm movements made in darkness to a visual target that was extinguished at the onset of each reach. Prerotation subjects pointed with both the right and left arms in alternating sets of eight movements. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
129
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(144 citation statements)
references
References 11 publications
14
129
1
Order By: Relevance
“…The idea that movement trajectory and final position are differentially controlled is also consistent with studies that have examined adaptation to novel forces (DiZio & Lackner, 1995;Lackner & DiZio, 1994) and visuomotor rotations (Sainburg & Wang, 2002;Wang & Sainburg, 2003. In the studies by Lackner and DiZio (DiZio & Lackner, 1995;Lackner & DiZio, 1994), participants reached to a target when adapting to Coriolis force fields, without any visual feedback.…”
Section: Differential Control Of Trajectory and Positionsupporting
confidence: 68%
See 2 more Smart Citations
“…The idea that movement trajectory and final position are differentially controlled is also consistent with studies that have examined adaptation to novel forces (DiZio & Lackner, 1995;Lackner & DiZio, 1994) and visuomotor rotations (Sainburg & Wang, 2002;Wang & Sainburg, 2003. In the studies by Lackner and DiZio (DiZio & Lackner, 1995;Lackner & DiZio, 1994), participants reached to a target when adapting to Coriolis force fields, without any visual feedback.…”
Section: Differential Control Of Trajectory and Positionsupporting
confidence: 68%
“…However, when no haptic information was available, movements became straighter but were still inaccurate. In a subsequent study of interlimb transfer, DiZio and Lackner (1995) demonstrated that only final position information transferred to the nonexposed limb. This clearly suggests that trajectory and position seem to be differentially controlled.…”
Section: Differential Control Of Trajectory and Positionmentioning
confidence: 97%
See 1 more Smart Citation
“…Factors such as joint torques (or muscle force; Scheidt et al 2000), limb impedance (Takahashi et al 2001;Burdet et al 2001), and the relative contribution of feedforward and feedback mechanisms (Dizio and Lackner 1995;see also Bagesteiro and Sainburg 2005) likely play an important role in the adaptation process. Thus, our focus on the control of the hand trajectory will need to be extended in future work to account for the role of such factors in the adaptation process.…”
Section: The Current Results Suggest That Internal Models May Not Invmentioning
confidence: 99%
“…The capacity for broad generalization seems to depend on multiple instances of local learning and a process of interpolation between individual examples (Atkeson, 1989;Gandolfo et al, 1996;Ghahramani and Wolpert, 1997;Malfait et al 2005;Mattar and Ostry, 2007a,b). Instances of generalization of dynamics learning have been described for interlimb movements, typically when movements, equivalent to those in the training condition, are repeated with the contralateral limb (Dizio and Lackner, 1995;CriscimagnaHemminger et al, 2003;Malfait and Ostry, 2004;Wang and Sainburg, 2004). Generalization for dynamics learning is also observed to movements that differ in amplitude and duration, but this is in the context of movements in a single direction (Goodbody and Wolpert, 1998).…”
Section: Introductionmentioning
confidence: 99%